New meanings of computer-based entertainment and communication among students in Poland during the COVID-19 pandemic - Mokras-Grabowska, Justyna; Mroczek-Żulicka, Aleksandra; Olasik, Marta (Quaestiones Geographicae, 2022)
This article is an attempt at investigating new meanings and significance of computer-based entertainment during the COVID-19 pandemic. The authors explore how and to what extent students in Poland have been using electronics for entertainment during the global crisis, what emotions appeared and whether they were able and willing to engage in an auto-reflexive process. The article presents the results of the questionnaire interview designed for the purposes of this particular study. The authors chose to reveal the multi-facetedness of the theme in question, i.e. focus on the possibilities and the future that computer-based etertainment offers, leading to transformations both externally and internally.